2014
DOI: 10.5812/hepatmon.19370
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Interleukin-10: A Likely Predictive Marker for Hepatitis B Virus-Related Acute-on-Chronic Liver Failure

Abstract: Background:The pathogenesis of HBV-related acute-on-chronic liver failure (HBV-ACLF) is mainly based on a heightened immune-inflammatory reaction; however, the intimate underlying mechanism remains unclear.Objectives:The aim of the study was to explore potential key immune molecular targets that could serve as early predictive markers for HBV-ACLF.Patients and Methods:Twenty-seven patients with acute exacerbation of chronic hepatitis B (CHB) (defined by: alanine transaminase ≥ 20 ULN, total bilirubin ≥ 5 ULN, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 25 publications
(30 reference statements)
3
19
0
Order By: Relevance
“…Furthermore, we also reported that nonsurvivals showed higher plasma IL‐10 level compared with survivals, and IL‐10 correlated with mortality of ACHBLF patients. These results were agreeable with previous studies . In the patients with liver failure, IL‐10 might impair the production of monocyte pro‐inflammatory cytokines and lead to the dysfunction of immune response .…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, we also reported that nonsurvivals showed higher plasma IL‐10 level compared with survivals, and IL‐10 correlated with mortality of ACHBLF patients. These results were agreeable with previous studies . In the patients with liver failure, IL‐10 might impair the production of monocyte pro‐inflammatory cytokines and lead to the dysfunction of immune response .…”
Section: Discussionsupporting
confidence: 93%
“…Based on the above results, we focused on the role of A20 in the pathogenesis of ACHBLF. A number of studies have shown that the immune‐inflammatory cytokines in the prophase or early phase of ACHBLF correspond to a high‐expression status, suggesting that cytokines play an important factor in the development of ACHBLF . Similarly, our present study showed elevated levels of several pro‐ and anti‐inflammatory cytokines in ACHBLF including IL‐1 β , IL‐6 and IL‐10.…”
Section: Discussionsupporting
confidence: 81%
“…Inflammatory cytokines IL‐1 β , IL‐6 and IL‐10 play crucial roles in ACHBLF pathogenesis . To evaluate the relationships between A20 expression and plasma levels of pro‐ or anti‐inflammatory mediators in patients with ACHBLF, we examined plasma concentrations of IL‐1 β , IL‐6 and IL‐10 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different markers and prognostic scores have been tested on their ability to stratify the risk of mortality in patients with compensated or decompensated liver cirrhosis as well as in patients with acute-on-chronic liver failure (ACLF). So far, biomarkers of systemic inflammation and infection have performed fairly well to distinguish patients with a stable disease course from those at higher risk of decompensation [2][3][4]. Moreover, biomarkers of macrophage activation and immune danger signals were demonstrated to predict outcome in patients with decompensated liver cirrhosis, especially in patients with alcoholic hepatitis [5].…”
Section: Introductionmentioning
confidence: 99%